SUICIDES OF FAMOUS ATHLETES OF MODERN TIME: STORIES AND REASONS - Nykyha, O. V.; Romanchuk, O. V.; Koval, R. S. (Rehabilitation and Recreation, 2025)
Introduction. Professional athletes often suffer from physical and psychological injuries, they are underconsiderable pressure due to the constant need to demonstrate their victories, the high level of competition, violations of fair play, etc. These factors can increase the risk of suicide among them.The aim of the work is to study the life, professional career, reasons and methods of suicide of famous athletes in the first quarter of the 21st century. We used general scientific (description and observation) and theoretical (analysis, synthesis, classification, explanation, and generalization) research methods to achieve the goal.Results. The present study analysed information on 336 male and 45 female athletes who committedsuicide between January 2000 and December 2024. All the data was taken from verified sources. The research demonstrated that for every instance of female athlete suicide, there were approximately nine instances of male athletes committing suicide. The highest number of male athlete suicides was recorded in 2019, the lowest in 2000, and the highest number of female athletes committed suicide in 2020. Since 2009, there has been an increase in the incidence of suicidal acts. A study revealed that male athletes were most prone to committing suicide between the ages of 30 and 49, while female athletes demonstrated a peak in suicide rates between the ages of 20 and 39. In the case of the 252 athletes whose method of suicide is known, hanging and gunshot wounds were the most prevalent. In the case of the 26 female athletes, the most prevalent underlying factors contributing to injury were found to be falls from a height and overdosesor poisoning with dangerous substances. It was not possible to ascertain the method of suicide of 84 male athletes and 19 female athletes due to an absence of relevant information.Research has identified a number of factors that have been demonstrated to increase the risk of suicide, including diseases and injuries, career development and achieved results, difficult social relationships and economic reasons. The behaviour of an athlete who is prone to cruelty, sudden mood swings, depression,and suicidal intentions always requires urgent action. In such a state, the individual’s actions can become a potential threat not only to themselves but also to their loved ones.Conclusions. In the contemporary context, the development of reliable algorithms for predicting and preventing suicide has become imperative. The identification of problems at an early stage and the prescription of appropriate treatment are of paramount importance. Furthermore, restrictions on access to firearms must be considered, along with the prevention of the transformation of suicide locations into attractive sites for the development of than atourism.